Integrated thermodynamic and kinetic model of homogeneous catalytic N‐oxidation processes. Issue 4 (13th December 2019) - Wang, Jingyao; Mannan, M. Sam; Wilhite, Benjamin A.
Abstract: The homogeneous phosphotungstic acid catalyzed N ‐oxidation of alkylpyridines by hydrogen peroxide has important applications in pharmaceutical and fine chemical industries. Current industry practice is to employ a semibatch reactor with gradual dosing of hydrogen peroxide into an alkylpyridine/catalyst solution under isothermal conditions. However, due to lack of understanding of reaction mechanism and thermodynamic behavior, this system is subject to significant risk of flammability, fires and explosions due to hydrogen peroxide decomposition. In this study, we conducted semibatch N ‐oxidation process in an isothermal reaction calorimeter (RC1) over a wide range of temperature, catalyst amount and oxidizer dosing rates. Reactor pressure, reaction heat generation rate and in situ FTIR spectra of liquid phase species were recorded in real‐time during experiments, and final product was quantified using HPLC and GC–MS analytical tools. We developed an integrated thermodynamic and kinetics model of homogeneous N ‐oxidation reaction based on experimental results and past literature findings. More specifically, Wilson excess Gibbs model was employed to estimate activity coefficients of highly nonideal liquid mixture. We found ideal gas law was satisfactory in calculating incondensable oxygen pressure. First principle reaction mechanism and kinetics parameters of (a) catalytic N ‐oxidation reaction; (b) catalytic hydrogen peroxide decomposition reaction; (c) noncatalytic N ‐oxidation reaction; (d) noncatalytic hydrogen peroxide decomposition reaction was derived based on experimental findings of this study and past literature. The proposed integrated thermodynamic model and kinetics model successfully predicted highly nonlinear reactor pressure, species concentration and reaction enthalpy generation rate profile of homogenous catalytic N ‐oxidation and H2 O2 decomposition reaction. The optimal reactions conditions with maximum N ‐oxide product yield and minimum reactor pressure and catalyst usage was theoretically identified and further verified by experiments. The obtained model can be used for inherently safer reactor design and applied to other homogeneous tungstic acid catalytic hydrogen peroxide oxidation processes.